1991
DOI: 10.1111/j.1432-1033.1991.tb16132.x
|View full text |Cite
|
Sign up to set email alerts
|

Autoprocessing of the HIV‐1 protease using purified wild‐type and mutated fusion proteins expressed at high levels in Escherichia coli

Abstract: Various constructs of the human immunodeficiency virus, type 1 (HIV-1) protease containing flanking Pol region sequences were expressed as fusion proteins with the maltose-binding protein of the malE gene of Escherichia coli. The full-length fusion proteins did not exhibit self-processing in E. coli, thereby allowing rapid purification by affinity chromatography on cross-linked amylose columns. Denaturation of the fusion protein in 5 M urea, followed by renaturation, resulted in efficient site-specific autopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 29 publications
3
37
0
Order By: Relevance
“…Louis et al reported that a fusion protein of human immunodeficiency virus type 1 protease (HIV-1) with MBP was not self-processed in E. coli cells, and Wan et al indicated that recombinant HIV-1 expressed as fusion proteins might affect the dimerization of this enzyme which is necessary to the formation of the protease active site, resulting in a reduction in toxicity to the host cells. 10,11) These results are consistent with the present observation that the fused proteins appeared to suppress effectively the folding-promoting activity of the Nterminal propeptide within the aqualysin-precursor, leading to greatly improved recovery of the mature enzyme.…”
Section: Characterization Of the Fusion Gene Productsupporting
confidence: 81%
See 1 more Smart Citation
“…Louis et al reported that a fusion protein of human immunodeficiency virus type 1 protease (HIV-1) with MBP was not self-processed in E. coli cells, and Wan et al indicated that recombinant HIV-1 expressed as fusion proteins might affect the dimerization of this enzyme which is necessary to the formation of the protease active site, resulting in a reduction in toxicity to the host cells. 10,11) These results are consistent with the present observation that the fused proteins appeared to suppress effectively the folding-promoting activity of the Nterminal propeptide within the aqualysin-precursor, leading to greatly improved recovery of the mature enzyme.…”
Section: Characterization Of the Fusion Gene Productsupporting
confidence: 81%
“…Louis et al have reported that selfprocessing of immunodeficiency virus type 1 protease (HIV-1) in E. coli was suppressed by fusing the protein with MBP. 10) We constructed fusion aqualysin I expression plasmids in which the signal peptide portion of the AQNÁC105 gene was replaced with a coding sequence of maltose binding protein (MBP), glutathione S-transferase (GST), or thioredoxin (Trx). When these fusion genes were introduced and were allowed to be expressed in E. coli, only a very low level of protease activity was detected in the crude extracts, but the activity was greatly enhanced on heat treatment of the extract at 70 C ( Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…HIV-1 NL4-3 protease genes containing the amino acid substitutions were generated as described (25). The mutant protease genes were cloned into the pMAL-P2 expression vector and expressed in Escherichia coli, and the fusion protein was purified as reported (29), with the exception of allowing the combination mutant proteases to autoprocess for longer times (16-48 h) before FPLC Mono S chromatography.…”
Section: Methodsmentioning
confidence: 99%
“…Enzyme Assay-Purified HIV-1 proteinase was prepared as described previously (16). Active site titration for the HIV-1 proteinase was performed with compound 3 (17).…”
Section: Methodsmentioning
confidence: 99%